The Impact of Esg Disclosure, Environmental Cost, and Corporate Reputation on Financial Performance - Driastuti, Melani; Nengzih, Nengzih; Oktris, Lin (Business and Investment Review, 2024)
This study was conducted to analyze the influence of ESG Disclosure, Environmental Costs, and Corporate Reputation on Financial Performance. Alareeni's study (2022) shows that ESG disclosure has an impact. This research uses companies listed on the Indonesia Stock Exchange in 2018-2022 as the population. The sample that meets the criteria in this study is 34 companies. The data analysis used is panel regression using E-Views 13 Application. The analysis results show the influence of ESG Disclosure, Environmental Cost, and Corporate Reputation variables simultaneously on the Company's Financial Performance. However, individually, only the Environmental Disclosure variable has a significant negative impact on the Company's Financial Performance variable.